2020
DOI: 10.1371/journal.pone.0230328
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of Chikungunya virus infection, progression, and cytokine profiles in human PMA-differentiated U937 and murine RAW264.7 monocyte derived macrophages

Abstract: Chikungunya virus (CHIKV) is a mosquito-borne alphavirus that causes rash, fever and severe polyarthritis that can last for years in humans. Murine models display inflammation and macrophage infiltration only in the adjacent tissues at the site of inoculation, showing no signs of systemic polyarthritis. Monocyte-derived macrophages are one cell type suspected to contribute to a systemic CHIKV infection. The purpose of this study was to analyze differences in CHIKV infection in two different cell lines, human U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 62 publications
2
4
0
Order By: Relevance
“…Since MBZM-N-IBT showed the ability to modulate diverse proinflammatory mediators, further validation was carried out in vivo . Most of the murine models of CHIKV display inflammation and macrophage infiltration only in the adjacent tissues at the site of inoculation, and no signs of systemic polyarthritis were observed ( 48 ), whereas in the current study the model showed CHIKV-induced arthritis-like symptoms, which are comparable to CHIKV disease pathogenesis in human. The molecule was able to demonstrate good effect to modulate this symptoms.…”
Section: Discussionsupporting
confidence: 43%
“…Since MBZM-N-IBT showed the ability to modulate diverse proinflammatory mediators, further validation was carried out in vivo . Most of the murine models of CHIKV display inflammation and macrophage infiltration only in the adjacent tissues at the site of inoculation, and no signs of systemic polyarthritis were observed ( 48 ), whereas in the current study the model showed CHIKV-induced arthritis-like symptoms, which are comparable to CHIKV disease pathogenesis in human. The molecule was able to demonstrate good effect to modulate this symptoms.…”
Section: Discussionsupporting
confidence: 43%
“…In addition to the 14 immune mediators of interest identified by the proteome profiler array, another five (CXCL-9, IL-12, PTX-3, IFN-α and IFN-β), which are known to be part of the immune response against CHIKV [20, 21], were selected for further testing with Luminex and ELISA (CXCL-10) assays, for samples from all eight donors.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the 14 immune mediators of interest identified by the proteome profiler array, another five (CXCL-9, IL-12, PTX-3, IFN-α and IFN-β), which are known to be part of the immune response against CHIKV [20,21], were selected for further testing with Luminex and ELISA (CXCL-10) assays, for samples from all eight donors. Expression of 11 immune mediators was detected in infected MDMs: chemokines CCL-2, CCL-3, CCL-4, RANTES, CXCL-9 and CXCL-10, cytokines IL-1Ra, IL-8, MIF and IFN-α, and the cytokine-induced protein PTX3 (summarized in Figs 4 and S5).…”
Section: Immune Mediators Secreted By Mdms In Response To Chikv Infec...mentioning
confidence: 99%
“…In addition to the mice model, earlier reports are also available on the CHIKV-driven pro-inflammatory cytokine burst and associated symptoms in human patient studies, in vivo ( 20 , 21 ). Accordingly, the effect of TLR4 inhibition could be further explored in experimental in vitro or in vivo setups with CHIKV-infected patient samples.…”
Section: Discussionmentioning
confidence: 99%